SENGKETA MEREK KANDUI DALAM PERSPEKTIF PERSAINGAN USAHA TIDAK SEHAT - Hanafi Zuhri; Saidin Saidin; Jelly Leviza (Smart Education, 2025)
Abstract: The problem in this study stems from the existence of unfair business competition arising from trademark registration applications in bad faith. The element of good faith has an important role in the trademark legal system in Indonesia to prevent disputes in the future. This study specifically analyzes the trademark dispute in the Medan District Court Decision Number 4 / Pdt.Sus-HKI / Merek / 2019 / PN Niaga Medan, which involves the registration of the KANDUI and KANDUI VILLAS trademarks by the defendant, even though the trademark has been previously used by the plaintiff, even the defendant himself is a manager at the plaintiff's lodging business. This study uses a normative juridical method with a statutory approach and a case approach. The issues studied include: (1) legal protection of trademarks according to the principle of good faith to prevent unfair business competition; (2) indications of unfair business competition practices in the KANDUI trademark dispute; and (3) the suitability of the judge's considerations in the decision with Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The results of the study indicate that the judge in the decision only emphasized the first to file principle as regulated in Article 3 of Law Number 20 of 2016, but was inconsistent with his considerations which had acknowledged the relevance of the first to use principle. In addition, the judge did not thoroughly examine the defendant's bad faith as stated in the plaintiff's petitum. Thus, although the judge's decision was formally in accordance with regulations, there were still weaknesses in upholding the principle of good faith which is an important instrument to prevent unfair business competition in the trademark legal regime.Keyword: Business competition, Brand, Bad faithÂ Abstrak: Permasalahan dalam penelitian ini berangkat dari adanya persaingan usaha tidak sehat yang timbul akibat permohonan pendaftaran merek dengan iktikad tidak baik. Unsur iktikad baik memiliki peran penting dalam sistem hukum merek di Indonesia agar tidak menimbulkan sengketa di kemudian hari. Penelitian ini secara khusus menganalisis sengketa merek pada Putusan Pengadilan Negeri Medan Nomor 4/Pdt.Sus-HKI/Merek/2019/PN Niaga Medan, yang melibatkan pendaftaran merekKANDUIdanKANDUI VILLASoleh tergugat, padahal merek tersebut telah lebih dahulu digunakan oleh penggugat, bahkan tergugat sendiri merupakan pengurus pada usaha penginapan milik penggugat. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan pendekatan kasus. Permasalahan yang dikaji meliputi: (1) perlindungan hukum terhadap merek menurut prinsip iktikad baik untuk mencegah persaingan usaha tidak sehat; (2) indikasi praktik persaingan usaha tidak sehat dalam sengketa merekKANDUI; serta (3) kesesuaian pertimbangan hakim dalam putusan tersebut dengan Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis. Hasil penelitian menunjukkan bahwa hakim dalam putusan tersebut hanya menekankan asasfirst to filesebagaimana diatur dalam Pasal 3 Undang-Undang Nomor 20 Tahun 2016, namun tidak konsisten dengan pertimbangannya yang sempat mengakui relevansi asasfirst to use. Selain itu, hakim tidak secara mendalam mengkaji iktikad tidak baik tergugat sebagaimana petitum penggugat. Dengan demikian, meskipun putusan hakim secara formil sesuai dengan regulasi, namun masih terdapat kelemahan dalam menegakkan prinsip iktikad baik yang menjadi instrumen penting untuk mencegah persaingan usaha tidak sehat dalam rezim hukum merekKata Kunci : Persaingan usaha, Merek, Iktikad tidak baik